The dark side of skin lightening: An international collaboration and review of a public health issue affecting dermatology - Samara Pollock, BA; Susan Taylor, MD; Oyetewa Oyerinde, MD; Sabrina Nurmohamed, MD; Ncoza Dlova, MD; Rashmi Sarkar, MD; Hassan Galadari, MD; Mônica Manela-Azulay, MD, PhD; Hae Shin Chung, MD; Evangeline Handog, MD; A. Shadi Kourosh, MD, MPH (Wolters Kluwer, 2021)
Skin lightening (SL) for cosmetic reasons is associated with profound negative impacts on well-being and adverse effects on the skin, resulting in immense challenges for dermatologists. Despite current regulations, lightening agents continue to dominate the cosmetic industry. In this review, our international team of dermatologists tackles the topic of SL as a global public health issue, one of great concern for both women's health and racial implications. We have examined SL in Africa, Asia, the Middle East, and the Americas. We aim to inspire a global discourse on how modern dermatologists can utilize scientific evidence and cultural competency to serve and protect patients of diverse skin types and backgrounds. In doing so, we hope to promote healthy skin and inclusive concepts of beauty in our patients and society.